Positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
By introducing specific types and contents of anions and cations into the polyanionic phosphate positive electrode material to form composite particles, the problem of poor electrochemical performance of existing materials is solved, and higher structural stability, conductivity and battery performance are achieved.
Patent Information
- Application Number
- CN202510019534.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The electrochemical performance of existing polyanionic phosphate positive electrode active materials is poor, resulting in poor cycle stability and rate performance in sodium ion batteries.
By simultaneously introducing specific types and contents of anions into the polyanionic phosphate positive electrode material, composite particles are formed, with the molecular formula Na4MxMn1-x/2V(PO4)3-x/3Nx, where 0.001≤x≤0.05, M is Li and/or K, and N is selected from one or more of F, Cl, Br and I.
The structural stability and conductivity of the positive electrode material have been significantly improved, the diffusion capacity of Na+ ions has been enhanced, the specific capacity, rate performance and cycle stability of the material have been improved, and the overall performance of the sodium ion battery has been improved.
Smart Images

Figure CN119833629A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a positive electrode material, a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art
[0002] Sodium-ion batteries are expected to be a good alternative to lithium-ion batteries due to their abundant sodium resources, low price, and similar electrochemical behavior to lithium. Due to their cost-effectiveness, environmental friendliness, safety, temperature adaptability, fast charging capability, and long cycle life, sodium-ion batteries are considered to be a promising alternative to new energy vehicle battery technology. With the advancement of technology, sodium-ion batteries are expected to become one of the mainstream battery technologies for new energy vehicles in the next few years, providing electric vehicles with more durable and safer power. Among them, the cathode, as an important component of sodium-ion batteries, has an important influence on the overall indicators of the battery. Common sodium-ion cathode materials such as layered transition metal oxides, Prussian blue compounds, and polyanionic compounds have the disadvantages of low specific energy and poor cycle stability, which will hinder commercial development and practical applications. Therefore, it is urgent to develop sodium-ion battery cathode materials with excellent electrochemical properties to meet practical needs.
[0003] NASICON phosphates in polyanionic compounds have the advantages of stable structure, high ionic conductivity and high voltage platform, and have become the key development target of positive electrode materials for sodium ion batteries. Among them, sodium vanadium manganese phosphate [Na4VMn(PO4)3] material has a high specific capacity (117mAh·g -1 ), but the material has poor electronic conductivity and undergoes irreversible phase transition during charge and discharge, resulting in a rapid decrease in capacity, leading to unsatisfactory cycle stability and rate performance. In order to improve the electrochemical performance of Na4VMn(PO4)3, researchers have mostly used ion doping techniques to overcome the inherent defects of the material. In recent years, some studies have shown that cation doping can effectively inhibit the conversion of Na4VMn(PO4)3 materials from Mn 3+ The Jahn-Teller effect induces lattice distortion and can increase the Na + vacancy concentration, thereby enhancing its ion diffusion ability; in addition, anion doping will also cause defects in the Na4VMn(PO4)3 material lattice, thereby broadening the transmission channel of sodium ions and improving the stability of the material.
[0004] In summary, the use of cation or anion doping alone can overcome the inherent defects of the Na4VMn(PO4)3 material to a certain extent, which is beneficial to improve its intrinsic conductivity. However, whether the NASICON-type phosphate crystals are doped with cations or anions alone, the lattice structure of the material will be unstable, thereby affecting the mechanical properties and thermal stability of the material. In addition, up to now, there is a lack of relevant research on the simultaneous doping of Na4VMn(PO4)3 materials with cations and anions, especially whether cations and anions can be synergistically doped.
[0005] Therefore, how to achieve the co-doping of anions and cations in the polyanionic phosphate positive electrode active material of the sodium ion battery so that it has better electrochemical performance is one of the important technical problems that need to be solved in this field. Summary of the invention
[0006] The main purpose of the present invention is to provide a positive electrode material and a preparation method thereof, a positive electrode plate and a sodium ion battery, so as to solve the problem that the electrochemical performance of polyanionic phosphate positive electrode active materials in the prior art is poor.
[0007] In order to achieve the above object, the present invention provides a positive electrode material in the first aspect, wherein the positive electrode material comprises composite particles, wherein the molecular formula of the composite particles is Na4M x Mn 1-x / 2 V(PO4) 3-x / 3 N x , wherein 0.001≤x≤0.05; M is Li and / or K, and N is selected from one or more of F, Cl, Br and I.
[0008] The present invention obtains a positive electrode material with particularly excellent electrochemical performance by co-doping anions and cations. The introduction of anions and cations can adjust the electronic structure of the positive electrode material and effectively increase the active sites of the positive electrode material, thereby improving the specific capacity of the positive electrode material. Specifically, compared with other types of anions and cations in the art, the F, Cl, Br and I halogen anions and Li and / or K alkali metal cations provided by the present invention can greatly improve the structural stability of polyanionic phosphate materials and the Na + The diffusion capacity of the positive electrode material enables the positive electrode material to obtain excellent cycle stability and rate performance. At the same time, the co-doping of anions and cations can also achieve the regulation of the microscopic morphology and size of the positive electrode material particles, thereby greatly improving the compaction density of the positive electrode material and enabling it to obtain higher energy density in practical applications.
[0009] Among them, the halogen anions have higher electronegativity than the common acid radicals such as sulfate, phosphate, and carbonate in the art, and can form stronger bonds with the original transition metal ions Mn and V in the positive electrode material, thereby significantly improving the structural stability and electrochemical performance of the positive electrode material. The alkali metal cations of Li and / or K, compared with other common cations in the art, such as Ca 2+ Mg 2+ etc., with a more suitable ionic radius, so as to be more easily embedded and de-embedded in the polyanionic phosphate structure, thereby improving the charge and discharge performance of the corresponding battery of the positive electrode material. At the same time, the above ions also show higher conductivity, so as to further optimize the electrochemical performance of the positive electrode material.
[0010] Based on the above anion and cation types, the doping amount of anion and cation is preferably uniform, that is, the stoichiometric number in the positive electrode material is 0.001≤x≤0.05, so as to more effectively adjust the electronic structure and enhance the Na + Ion migration and the formation of new active sites enable the positive electrode material to exhibit higher electrochemical performance.
[0011] In particular, in addition to the selection of the types of the above-mentioned anions and cations themselves and the doping amount, what is more important is the coordination relationship between the two doping elements and the polyanionic phosphate positive electrode material matrix. The polyanionic phosphate positive electrode material itself has a high theoretical specific capacity and good cycle stability, and when the above-mentioned anions and cations are introduced simultaneously in a specific doping amount, its electrochemical performance can be further improved. Compared with other types of positive electrode active materials, such as olivine-type phosphates, the polyanionic phosphates involved in the present invention have better compatibility and coordination with the above-mentioned anions and cations, and ultimately a positive electrode with better electrochemical performance can be obtained. Therefore, the doping of anions and cations can enhance structural stability, improve electrical conductivity, and promote ion migration, thereby improving the electrochemical performance of the positive electrode material. This synergistic effect makes the polyanionic phosphate positive electrode material have a more significant advantage in performance.
[0012] In some embodiments, in the molecular formula of the composite particle, 0.001≤x≤0.01; M is Li and / or K, and N is selected from one or more of F, Br and I.
[0013] In this embodiment, in the molecular formula of the composite particles, 0.001≤x≤0.01, thereby better avoiding the increase of the internal resistance of the positive electrode material and the decrease of the cycle stability due to the destruction of the positive electrode material structure. At the same time, preferably M is Li and / or K, and N is selected from one or more of F, Br and I.
[0014] In some embodiments, the molecular formula of the composite particles is preferably Na4M 0.01 Mn 0.995V(PO4) 2.997 N 0.01 , wherein M is Li and / or K, and N is selected from one or more of F, Br and I; or, the molecular formula of the composite particle is Na4M 0.001 Mn 0.9995 V(PO4) 2.9997 N 0.001 , wherein M is Li and / or, and N is F. Under the above optimized molecular structure, the doped anions and cations can cooperate better, thereby obtaining a positive electrode material with better electrochemical performance.
[0015] In some embodiments, considering the changes in the molecular structure and electronic structure of the phosphate cathode material due to anion and cation doping, the molecular formula of the composite particles is preferably Na4K 0.01 Mn 0.995 V(PO4) 2.997 F 0.01 、Na4Li 0.01 Mn 0.995 V(PO4) 2.997 F 0.01 、Na4K 0.01 Mn 0.995 V(PO4) 2.997 Br 0.01 、Na4K 0.01 Mn 0.995 V(PO4) 2.997 I 0.01 、Na4K 0.001 Mn 0.9995 V(PO4) 2.9997 F 0.001 or Na4K 0.05 Mn 0.975 V(PO4) 2.983 F 0.05 , and thus obtained a positive electrode material with better electrochemical performance and better stability.
[0016] Furthermore, in order to further improve the stability and conductivity of the positive electrode material, the positive electrode material preferably also includes a carbon coating layer coated on the outer surface of the composite particles, and the mass fraction of the carbon coating layer is 1% to 5% based on the total weight of the positive electrode material as 100%.
[0017] The second aspect of the present invention provides a method for preparing a positive electrode material, the method comprising: preparing a sodium source, a doping element source, a manganese source, a vanadium source and a phosphorus source into a mixed slurry; drying and calcining the mixed slurry in sequence to obtain a positive electrode material; wherein the positive electrode material comprises composite particles, the molecular formula of the composite particles is Na4M x Mn 1-x / 2 V(PO4)3-x / 3N x , 0.001≤x≤0.05; M is Li and / or K, and N is selected from one or more of F, Cl, Br and I.
[0018] With respect to the above-mentioned positive electrode material, the present invention provides a preparation method thereof accordingly. The preparation method is simple to operate and easy to control, and can optimize the reaction process to a greater extent, so as to prepare a positive electrode material with excellent electrochemical performance at a lower manufacturing cost.
[0019] In some embodiments, the calcination includes the following steps: a first stage calcination at a temperature of 320°C to 370°C and a holding time of 3h to 5h; and a second stage calcination at a temperature of 700°C to 750°C and a holding time of 7h to 9h.
[0020] The present invention refines the calcination process into two stages of calcination, which helps to better achieve the doping of anions and cations, and can also better inhibit the degradation of the structure of the polyanionic phosphate positive electrode material itself, thereby enhancing its structural stability and electrochemical performance.
[0021] In order to better protect the structure of the positive electrode material and reduce the introduction and generation of impurities, it is preferred that both the first and second calcinations are carried out under the protection of an inert gas, and more preferably the inert gas is argon and / or nitrogen. Thus, a positive electrode material with higher electrochemical performance and better stability is obtained, and ultimately the specific capacity and long cycle stability of the sodium ion battery prepared therefrom are higher.
[0022] Furthermore, in order to remove moisture more quickly and evenly, reduce material agglomeration, and optimize the microstructure and density of the positive electrode material, the drying is spray drying, and the air inlet temperature of the spray drying is 200°C to 250°C, and the air outlet temperature is 100°C to 140°C.
[0023] In some embodiments, the doping element source is selected from one or more of potassium fluoride, lithium fluoride, potassium bromide and potassium iodide. The above doping element source can more significantly optimize the molecular structure and electronic structure of the positive electrode material without introducing other impurity elements, so as to more effectively improve the electrochemical performance and structural stability of the positive electrode material.
[0024] In some embodiments, the sodium source is selected from one or more of sodium acetate, sodium carbonate, sodium hydroxide and sodium nitrate; and / or the phosphorus source is selected from one or more of diammonium phosphate, monoammonium phosphate, ammonium phosphate and phosphoric acid. The selection of the sodium source and the phosphorus source has an important influence on the synthesis process and the final performance of the positive electrode material. The present invention can optimize the synthesis conditions of the positive electrode material and improve the consistency and stability of the material by adjusting the types of the two as above.
[0025] In some embodiments, the manganese source is selected from one or more of manganese acetate tetrahydrate, manganese nitrate, manganese phosphate and manganese oxalate; and / or the vanadium source is selected from one or more of ammonium metavanadate, ammonium vanadate and ammonium sulfate. The selection of the manganese source and the vanadium source can affect the electronic structure and ion diffusion path of the positive electrode material. By optimizing the two respectively as above, the electronic conductivity and ion diffusion efficiency of the positive electrode material can be further improved.
[0026] The third aspect of the present invention provides a positive electrode sheet, which includes the above-mentioned positive electrode material, or includes the positive electrode material prepared by the preparation method of the above-mentioned positive electrode material. The positive electrode material provided by the present invention has excellent electrochemical performance and stability, so when used as an active material of the positive electrode sheet, the corresponding positive electrode sheet also has high energy density, long cycle life and excellent electrochemical stability, thereby significantly improving the overall performance of the battery.
[0027] The fourth aspect of the present invention provides a sodium ion battery, comprising the above-mentioned positive electrode plate. The positive electrode plate provided by the present invention exhibits high energy density and long cycle life because it contains a positive electrode material with excellent electrochemical properties. Therefore, when the positive electrode plate is applied to a sodium ion battery, the sodium ion battery also exhibits high discharge specific capacity and long cycle stability accordingly.
[0028] The present invention simultaneously introduces specific types and contents of anions and cations into the polyanionic phosphate positive electrode active material, so that the two produce a good synergistic effect, thereby greatly improving the intrinsic conductivity and structural stability of the positive electrode material, while achieving the regulation of its particle morphology and size, promoting a significant improvement in the comprehensive performance of the material such as specific capacity, rate performance, cycle stability and compaction density, and greatly promoting the industrial application of the material.
[0029] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 The XRD patterns of the positive electrode materials obtained in Example 1 and Comparative Example 1;
[0032] Figure 2 The SEM characterization results of the positive electrode materials obtained in Example 1 and Comparative Example 1 are shown in FIG. Figure 2 (a) and Figure 2 (b) is the SEM characterization result of the positive electrode material obtained in Example 1, Figure 2 (c) and Figure 2 (d) is the SEM characterization result of the positive electrode material obtained in Comparative Example 1. DETAILED DESCRIPTION
[0033] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0035] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0037] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0038] As described in the background art, the polyanionic phosphate positive electrode active materials in the prior art have poor chemical properties. In order to solve the above technical problems, the first aspect of the present invention provides a positive electrode material, which includes composite particles, the molecular formula of the composite particles is Na4M x Mn 1-x / 2 V(PO4) 3-x / 3 N x , wherein 0.001≤x≤0.05; M is Li and / or K, and N is selected from one or more of F, Cl, Br and I.
[0039] The present invention obtains a positive electrode material with particularly excellent electrochemical performance by co-doping anions and cations. The introduction of anions and cations can adjust the electronic structure of the positive electrode material and effectively increase the active sites of the positive electrode material, thereby improving the specific capacity of the positive electrode material. Specifically, compared with other types of anions and cations in the art, the F, Cl, Br and I halogen anions and Li and / or K alkali metal cations provided by the present invention can greatly improve the structural stability of polyanionic phosphate materials and the Na + The diffusion capacity of the positive electrode material enables the positive electrode material to obtain excellent cycle stability and rate performance. At the same time, the co-doping of anions and cations can also achieve the regulation of the microscopic morphology and size of the positive electrode material particles, thereby greatly improving the compaction density of the material and enabling it to obtain higher energy density in practical applications.
[0040] Among them, the halogen anions have higher electronegativity than the common acid radicals such as sulfate, phosphate, and carbonate in the art, and can form stronger bonds with the original transition metal ions Mn and V in the positive electrode material, thereby significantly improving the structural stability and electrochemical performance of the positive electrode material. The alkali metal cations of Li and / or K, compared with other common cations in the art, such as Ca 2+ Mg 2+ etc., with a more suitable ionic radius, so as to be more easily embedded and de-embedded in the polyanionic phosphate structure, thereby improving the charge and discharge performance of the secondary battery prepared with the positive electrode material. At the same time, the above ions also show higher conductivity, so as to further optimize the electrochemical performance of the positive electrode material.
[0041] Based on the above anion and cation types, the doping amount of anion and cation is preferably uniform, that is, the stoichiometric number in the positive electrode material is 0.001≤x≤0.05, so as to more effectively adjust the electronic structure and enhance the Na + Ion migration and the formation of new active sites enable the positive electrode material to exhibit higher electrochemical performance.
[0042] In particular, in addition to the selection of the types of the above-mentioned anions and cations themselves and the doping amount, what is more important is the coordination relationship between the two doping elements and the polyanionic phosphate positive electrode material matrix. The polyanionic phosphate positive electrode material itself has a high theoretical specific capacity and good cycle stability, and when the above-mentioned anions and cations are introduced simultaneously in a specific doping amount, its electrochemical performance can be further improved. Compared with other types of positive electrode active materials, such as olivine-type phosphates, the polyanionic phosphates involved in the present invention have better compatibility and coordination with the above-mentioned anions and cations, and ultimately a positive electrode with better electrochemical performance can be obtained. Therefore, the doping of anions and cations can enhance structural stability, improve electrical conductivity, and promote ion migration, thereby improving the electrochemical performance of the positive electrode material. This synergistic effect makes the polyanionic phosphate positive electrode material have a more significant advantage in performance.
[0043] In some embodiments, in the molecular formula of the composite particle, 0.001≤x≤0.01; M is Li and / or K, and N is selected from one or more of F, Br and I.
[0044] In this embodiment, in the molecular formula of the composite particles, 0.001≤x≤0.01, thereby better avoiding the increase of the internal resistance of the positive electrode material and the decrease of the cycle stability due to the destruction of the positive electrode material structure. At the same time, preferably M is Li and / or K, and N is selected from one or more of F, Br and I.
[0045] In some embodiments, the molecular formula of the composite particles is preferably Na4M 0.01 Mn 0.995 V(PO4) 2.997 N 0.01 , wherein M is Li and / or K, and N is selected from one or more of F, Br and I; or, the molecular formula of the composite particle is Na4M 0.001 Mn 0.9995 V(PO4) 2.9997 N 0.001 , wherein M is Li and / or K, and N is F. Under the above optimized molecular structure, the doped anions and cations can cooperate better, thereby obtaining a positive electrode material with better electrochemical performance.
[0046] In some embodiments, considering the changes in the molecular structure and electronic structure of the phosphate cathode material due to anion and cation doping, the molecular formula of the composite particles is preferably Na4K 0.01 Mn 0.995 V(PO4) 2.997 F 0.01 、Na4Li 0.01 Mn 0.995 V(PO4) 2.997 F 0.01 、Na4K0.01 Mn 0.995 V(PO4) 2.997 Br 0.01 、Na4K 0.01 Mn 0.995 V(PO4) 2.997 I 0.01 、Na4K 0.001 Mn 0.9995 V(PO4) 2.9997 F 0.001 or Na4K 0.05 Mn 0.975 V(PO4) 2.983 F 0.05 , and thus obtained a positive electrode material with better electrochemical performance and better stability.
[0047] And, in order to further improve the stability and conductivity of the positive electrode material, the positive electrode material preferably further includes a carbon coating layer coated on the outer surface of the composite particles, and the mass fraction of the carbon coating layer is 1% to 5% based on the total weight of the positive electrode material as 100%. More preferably, the mass fraction of the carbon coating layer is 2.0% to 2.5% based on the total weight of the positive electrode material as 100%.
[0048] The second aspect of the present invention provides a method for preparing a positive electrode material, the method comprising: preparing a sodium source, a doping element source, a manganese source, a vanadium source and a phosphorus source into a mixed slurry; drying and calcining the mixed slurry in sequence to obtain a positive electrode material; wherein the positive electrode material comprises composite particles, the molecular formula of the composite particles is Na4M x Mn 1-x / 2 V(PO4) 3-x / 3N x , 0.001≤x≤0.05; M is Li and / or K, and N is selected from one or more of F, Cl, Br and I.
[0049] With respect to the above-mentioned positive electrode material, the present invention provides a preparation method thereof accordingly. The preparation method is simple to operate and easy to control, and can optimize the reaction process to a greater extent, so as to prepare a positive electrode material with excellent electrochemical performance at a lower manufacturing cost.
[0050] Furthermore, in order to introduce a more uniform carbon layer on the surface of the positive electrode material to improve its conductivity, the step of preparing the mixed slurry includes: preparing the carbon source into a carbon source solution with a concentration of 0.18 mol / L to 0.20 mol / L, and adding a sodium source, a doping element source, a manganese source, a vanadium source and a phosphorus source to the carbon source solution, and obtaining a mixed slurry after stirring. At the same time, the carbon source is preferably selected from one or more of glucose, monohydrated citric acid, and soluble starch.
[0051] In some embodiments, the calcination includes the following steps: a first stage calcination at a temperature of 320°C to 370°C and a holding time of 3h to 5h; a second stage calcination at a temperature of 700°C to 750°C and a holding time of 7h to 9h. The present invention refines the calcination process into two stages, thereby helping to better achieve the doping of anions and cations, and also better inhibiting the degradation of the structure of the polyanionic phosphate cathode material itself, thereby enhancing its structural stability and electrochemical performance.
[0052] Among them, in order to better protect the structure of the positive electrode material and reduce the introduction and generation of impurities, the first calcination and the second calcination are both carried out under the protection of an inert gas. At the same time, the inert gas is more preferably argon and / or nitrogen, so as to obtain a positive electrode material with higher electrochemical performance and better stability, and ultimately the prepared sodium ion battery has a higher specific capacity and long cycle stability.
[0053] Furthermore, in order to remove moisture more quickly and evenly, reduce material agglomeration, and optimize the microstructure and density of the positive electrode material, the drying is spray drying, and the air inlet temperature of the spray drying is 200°C to 250°C, and the air outlet temperature is 100°C to 140°C.
[0054] In some embodiments, the doping element source is selected from one or more of potassium fluoride, lithium fluoride, potassium bromide and potassium iodide. The above doping element source can more significantly optimize the molecular structure and electronic structure of the positive electrode material without introducing other impurity elements, so as to more effectively improve the electrochemical performance and structural stability of the positive electrode material.
[0055] Further, the sodium source is selected from one or more of sodium acetate, sodium carbonate, sodium hydroxide and sodium nitrate; and / or the phosphorus source is selected from one or more of diammonium phosphate, monoammonium phosphate, ammonium phosphate and phosphoric acid. The selection of the sodium source and the phosphorus source has an important influence on the synthesis process and final performance of the positive electrode material. The present invention can optimize the synthesis conditions of the positive electrode material and improve the consistency and stability of the material by adjusting the types of the two as above.
[0056] Furthermore, the manganese source is selected from one or more of manganese acetate tetrahydrate, manganese nitrate, manganese phosphate and manganese oxalate; and / or the vanadium source is selected from one or more of ammonium metavanadate, ammonium vanadate and ammonium sulfate. The selection of the manganese source and the vanadium source can affect the electronic structure and ion diffusion path of the positive electrode material. By optimizing the two respectively as above, the electronic conductivity and ion diffusion efficiency of the positive electrode material can be further improved.
[0057] A third aspect of the present invention provides a positive electrode plate, which includes the above-mentioned positive electrode material, or includes the positive electrode material prepared by the above-mentioned method for preparing the positive electrode material.
[0058] The positive electrode material provided by the present invention has excellent electrochemical properties and stability. Therefore, when used as the active material of the positive electrode plate, the corresponding positive electrode plate also has high energy density, long cycle life and excellent electrochemical stability, thereby significantly improving the overall performance of the battery.
[0059] A fourth aspect of the present invention provides a sodium ion battery comprising the above-mentioned positive electrode plate.
[0060] The positive electrode plate provided by the present invention exhibits high energy density and long cycle life because it contains positive electrode materials with excellent electrochemical properties. Therefore, when the positive electrode plate is used in a sodium ion battery, the sodium ion battery also correspondingly exhibits high discharge specific capacity and long cycle stability.
[0061] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0062] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0063] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0064] 1. Preparation method
[0065] Example 1
[0066] A method for preparing a positive electrode material:
[0067] Weigh citric acid monohydrate (C6H8O7·H2O) and add it to deionized water, and stir to prepare a transparent solution with a C6H8O7·H2O concentration of 0.18 mol / L.
[0068] Sodium source sodium acetate (CH3COONa), doping element source potassium fluoride (KF), manganese source manganese acetate tetrahydrate [(CH3COO)2Mn·4H2O], vanadium source ammonium metavanadate (NH4VO3) and phosphorus source ammonium dihydrogen phosphate (NH4H2PO4) were weighed in a molar ratio of 4:0.001:0.9995:1:2.9997, and added to the above solution in sequence, and then the solution was continued to be fully stirred to obtain a mixed slurry.
[0069] The mixed slurry was spray dried and granulated to obtain a brown-yellow precursor material. During the spray drying process, the air inlet temperature was 220°C and the air outlet temperature was 120°C. The brown-yellow precursor material was placed in a sintering furnace in an argon atmosphere and heated to 350°C at a heating rate of 5°C / min and kept warm for 4h, i.e., the first stage of calcination, and then calcined at a rate of 5°C min- 1 The temperature is raised to 720°C at a heating rate and kept at this temperature for 8h, i.e. the second stage of calcination, to complete sintering.
[0070] After sintering, the black powder obtained is the carbon-coated K+ and F- co-doped Na4MnV(PO4)3 material, whose molecular formula is Na4K 0.001 Mn 0.9995 V(PO4) 2.9997 F 0.001 Meanwhile, based on the total weight of the obtained black powder being 100%, the mass fraction of the carbon coating layer is 2.4%.
[0071] The XRD pattern of the obtained positive electrode material is shown in Figure 1 , SEM characterization results are shown in Figure 2 (a) and Figure 2 (b), where Figure 2 (a) The scale bar is 15 μm. Figure 2 The scale bar in (b) is 5 μm.
[0072] from Figure 1 It can be seen that the positive electrode material doped with K and F ions obtained in Example 1 still has the same crystal form as the undoped Na4MnV(PO4)3. In other words, after the synergistic doping of K+ and F-, the crystal form of the obtained positive electrode material is not destroyed and is still a polyanionic phosphate structure, and its corresponding structural advantages are also retained, so that it can show more superior electrochemical performance on this basis.
[0073] Example 2
[0074] A method for preparing a positive electrode material:
[0075] The only difference between this embodiment and embodiment 1 is that the molar ratio of the sodium source sodium acetate (CH3COONa), the doping element source potassium fluoride (KF), the manganese source manganese acetate tetrahydrate [(CH3COO)2Mn·4H2O], the vanadium source ammonium metavanadate (NH4VO3) and the phosphorus source diammonium phosphate (NH4H2PO4) is changed to 4:0.01:0.995:1:2.997.
[0076] The black powder obtained is the carbon-coated K+ and F- co-doped Na4MnV(PO4)3 material, and its molecular formula is Na4K 0.01 Mn 0.995 V(PO4) 2.997F 0.01 .
[0077] Example 3
[0078] A method for preparing a positive electrode material:
[0079] The only difference between this embodiment and embodiment 1 is that the molar ratio of the sodium source sodium acetate (CH3COONa), the doping element source potassium fluoride (KF), the manganese source manganese acetate tetrahydrate [(CH3COO)2Mn·4H2O], the vanadium source ammonium metavanadate (NH4VO3) and the phosphorus source diammonium phosphate (NH4H2PO4) is changed to 4:0.05:0.975:1:2.983.
[0080] The black powder obtained is the carbon-coated K+ and F- co-doped Na4MnV(PO4)3 material, and its molecular formula is Na4K 0.04 Mn 0.975 V(PO4) 2.983 F 0.05 .
[0081] Example 4
[0082] A method for preparing a positive electrode material:
[0083] The only difference between this embodiment and embodiment 2 is that an equimolar amount of lithium fluoride (LiF) is used to replace potassium fluoride (KF) to obtain a carbon-coated Li + and F - Co-doped Na4MnV(PO4)3 material, whose molecular formula is Na4Li 0.01 Mn 0.995 V(PO4) 2.997 F 0.01 .
[0084] Example 5
[0085] A method for preparing a positive electrode material:
[0086] The only difference between this embodiment and embodiment 2 is that potassium bromide (KBr) is used in an equimolar amount to replace potassium fluoride (KF) to obtain a carbon-coated K+ and Br-coated Na4MnV(PO4)3 material, the molecular formula of which is Na4K 0.01 Mn 0.995 V(PO4) 2.997 Br 0.01 .
[0087] Example 6
[0088] A method for preparing a positive electrode material:
[0089] The only difference between this embodiment and embodiment 2 is that an equimolar amount of potassium iodide (KI) is used instead of potassium fluoride (KF) to obtain carbon-coated K + and I - Co-doped Na4MnV(PO4)3 material, whose molecular formula is Na4K 0.01 Mn 0.995 V(PO4) 2.997 I 0.01 .
[0090] Example 7
[0091] A method for preparing a positive electrode material:
[0092] The only difference between this embodiment and embodiment 1 is that the air inlet temperature is changed to 280°C and the air outlet temperature is changed to 80°C during the spray drying process.
[0093] Example 8
[0094] A method for preparing a positive electrode material:
[0095] The only difference between this embodiment and embodiment 1 is that the air inlet temperature is changed to 180°C and the air outlet temperature is changed to 160°C during the spray drying process.
[0096] Example 9
[0097] A method for preparing a positive electrode material:
[0098] The only difference between this embodiment and embodiment 1 is that the temperature of the first calcination stage is changed to 320° C. and the holding time is changed to 5 h; the temperature of the second calcination stage is changed to 700° C. and the holding time is changed to 9 h.
[0099] Example 10
[0100] A method for preparing a positive electrode material:
[0101] The only difference between this embodiment and embodiment 1 is that the temperature of the first calcination stage is changed to 370° C. and the holding time is changed to 3 h; the temperature of the second calcination stage is changed to 750° C. and the holding time is changed to 7 h.
[0102] Embodiment 11
[0103] A method for preparing a positive electrode material:
[0104] The only difference between this embodiment and embodiment 1 is that the temperature of the first calcination stage is changed to 300° C. and the holding time is changed to 6 h; the temperature of the second calcination stage is changed to 780° C. and the holding time is changed to 6 h.
[0105] Example 12
[0106] A method for preparing a positive electrode material:
[0107] The only difference between this embodiment and embodiment 1 is that the temperature of the first calcination stage is changed to 400° C. and the holding time is changed to 2 h; the temperature of the second calcination stage is changed to 680° C. and the holding time is changed to 10 h.
[0108] Embodiment 13
[0109] A method for preparing a positive electrode material:
[0110] The only difference between this embodiment and embodiment 1 is that the second stage calcination is not performed and the sintering furnace used for calcination is not protected by argon atmosphere.
[0111] Comparative Example 1
[0112] A method for preparing a positive electrode material:
[0113] The only difference between this comparative example and Example 1 is that the doping element source KF is not added, and the molar ratio of the sodium source sodium acetate (CH3COONa), the manganese source manganese acetate tetrahydrate [(CH3COO)2Mn·4H2O], the vanadium source ammonium metavanadate (NH4VO3) and the phosphorus source ammonium dihydrogen phosphate (NH4H2PO4) is changed to 4:1:1:3.
[0114] The obtained black powder is the carbon-coated undoped Na4MnV(PO4)3 material.
[0115] The XRD pattern of the obtained positive electrode material is shown in Figure 1 , SEM characterization results are shown in Figure 2 (c) and Figure 2 (d), where Figure 2 (c) The scale bar is 15 μm. Figure 2 The scale bar in (d) is 5 μm.
[0116] Comparative Example 2
[0117] A method for preparing a positive electrode material:
[0118] The difference between this comparative example and Example 1 is that the molar ratio of sodium acetate (CH3COONa), doping element source potassium fluoride (KF), manganese source manganese acetate tetrahydrate [(CH3COO)2Mn·4H2O], vanadium source ammonium metavanadate (NH4VO3) and phosphorus source ammonium dihydrogen phosphate (NH4H2PO4) is changed to 4:0.0005:0.99975:1:2.9998, and K + and F - Co-doped Na4MnV(PO4)3 material, whose molecular formula is Na4K 0.0005 Mn 0.99975 V(PO4) 2.9998F 0.0005 .
[0119] Comparative Example 3
[0120] A method for preparing a positive electrode material:
[0121] The difference between this comparative example and Example 1 is that the molar ratio of sodium acetate (CH3COONa), doping element source potassium fluoride (KF), manganese source manganese acetate tetrahydrate [(CH3COO)2Mn·4H2O], vanadium source ammonium metavanadate (NH4VO3) and phosphorus source ammonium dihydrogen phosphate (NH4H2PO4) is changed to 4:0.1:0.95:1:2.97, and K + and F - Co-doped Na4MnV(PO4)3 material, whose molecular formula is Na4K 0.1 Mn 0.95 V(PO4) 2.97 F 0.1 .
[0122] Comparative Example 4
[0123] A method for preparing a positive electrode material:
[0124] The difference between this comparative example and Example 1 is that an equimolar amount of potassium sulfate (K2(SO4)) is used instead of potassium fluoride (KF) to obtain carbon-coated K + and SO4 2- Co-doped Na4MnV(PO4)3 material, whose molecular formula is Na4K 0.001 Mn 0.9995 V(PO4) 2.9997 (SO4) 0.0005 .
[0125] Comparative Example 5
[0126] A method for preparing a positive electrode material:
[0127] The difference between this comparative example and Example 1 is that an equimolar amount of calcium fluoride (CaF2) is used to replace potassium fluoride (KF) to obtain carbon-coated Ca 2+ and F - The co-doped Na4MnV(PO4)3 material has the molecular formula Na4Ca 0.001 Mn 0.9995 V(PO4) 2.997 F 0.002 .
[0128] 2. Test Method
[0129] Compacted density: According to GB / T 24533, the compacted density of the positive electrode material powder obtained in each example and comparative example was measured.
[0130] Battery preparation and performance testing: The positive electrode material, Super P (conductive additive) and binder (PVDF+NMP) were ground and mixed in a mass ratio of 7:2:1, and then the mixed slurry was evenly applied to the dry aluminum foil using a square device (applicator). The coated slurry was placed in a vacuum oven at 100°C for 12 hours, and after cooling to room temperature, it was cut into circular electrode sheets using a 12mm mold. The mass of the electrode sheets was then weighed using an electronic balance. Each electrode sheet was weighed three times to obtain an average value, and finally placed in a 100°C drying oven for storage. The battery assembly process was carried out in a glove box with an argon atmosphere. The prepared electrode sheet is placed in the transition chamber of the glove box, and the vacuum-replenishment is repeated three times and then brought into the glove box. Part of the sodium block is cut and flattened, and a 12mm mold is used to punch a round sodium sheet. Then the gasket and the sodium sheet are placed in the negative electrode shell and flattened, and then the diaphragm is placed therein, the electrolyte is dripped, and the electrode sheet is placed (the positive electrode material side faces the diaphragm). Finally, the gasket and the spring sheet are placed in respectively, and the positive electrode shell is buckled and assembled into a CR2032 button battery. Finally, the battery is sealed on a battery sealing machine, and the electrochemical test is performed after standing for about 6 hours at room temperature. The electrolyte is a mixture of 1M NaClO4, 95% PC and 5% FEC, and the diaphragm is glass fiber. The battery samples corresponding to the positive electrode materials prepared in each embodiment and comparative example are obtained, and each battery sample is charged and discharged at 2.5V to 3.8V at 25°C, and its discharge specific capacity at 0.1C and 1C is tested respectively. The cycle performance was tested using a Xinwei electrochemical test cabinet to obtain the specific capacity drop rate after 500 cycles at 1C.
[0131] The above test results are shown in Table 1.
[0132] Table 1
[0133]
[0134]
[0135] III. Analysis of test results of various embodiments and comparative examples
[0136] It can be seen from the above results that the above embodiments of the present invention achieve the preparation of positive electrode materials with better electrochemical performance. Specifically:
[0137] Comparing the embodiments with the comparative examples, it can be seen that the Na4M x Mn 1-x / 2 V(PO4) 3-x / 3 N xThe molecular formula of the composite particles, when 0.001≤x≤0.05, M is Li and / or K, and N is selected from one or more of F, Cl, Br and I, the obtained positive electrode material has better electrochemical performance. When used as a positive electrode material, the prepared battery exhibits higher specific capacity and better cycle stability.
[0138] Comparing Example 3 with Example 1, Example 2, Example 4, Example 5 and Example 6, it can be seen that in addition to the selection of anion and cation types, the doping amount matched with the type also has an impact on the performance of the obtained positive electrode material. And from these examples, it can be seen that when the molecular formula of the composite particle is Na4M 0.01 Mn 0.995 V(PO4) 2.997 N 0.01 , wherein M is Li and / or K, and N is selected from one or more of F, Br and I; or, the molecular formula of the composite particle is Na4M 0.001 Mn 0.9995 V(PO4) 2.9997 N 0.001 , where M is Li and / or K and N is F, the resulting cathode material exhibits superior electrochemical performance. 0.01 Mn 0.995 V(PO4) 2.997 F 0.01 、Na4Li 0.01 Mn 0.995 V(PO4) 2.997 F 0.01 、Na4K 0.01 Mn 0.995 V(PO4) 2.997 Br 0.01 、Na4K 0.01 Mn 0.995 V(PO4) 2.997 I 0.01 、Na4K 0.001 Mn 0.9995 V(PO4) 2.9997 F 0.001 or Na4K 0.05 Mn 0.975 V(PO4) 2.983 F 0.05 When the obtained positive electrode material is used to prepare the battery, the corresponding battery sample has higher specific capacity and cycle stability.
[0139] By comparing Example 7 and Example 8 with Example 1, it can be seen that when the drying is spray drying, and the air inlet temperature of the spray drying is 200°C to 250°C, and the air outlet temperature is 100°C to 140°C, it can reduce material agglomeration, optimize the microstructure and density of the positive electrode material, and make it exhibit higher electrochemical performance.
[0140] Comparing Example 9 and Example 10 with Example 1, Example 11 and Example 12, it can be seen that the temperature of the first stage calcination is preferably 320°C to 370°C, and the holding time is preferably 3h to 5h. At the same time, the temperature of the second stage calcination is preferably 700°C to 750°C, and the holding time is preferably 7h to 9h, which helps to better achieve the doping of anions and cations. This calcination temperature can also better inhibit the degradation of the structure of the polyanionic phosphate positive electrode material itself, and enhance its structural stability and electrochemical performance.
[0141] Comparing Example 13 with Example 1, it can be seen that by dividing the calcination process into two stages, and both the first and second stages of calcination are carried out under the protection of an inert gas, a positive electrode material with higher electrochemical performance and better stability can be obtained, and ultimately the specific capacity and long-cycle stability of the prepared sodium ion battery can be higher.
[0142] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes composite particles, the molecular formula of which is Na4M x Mn 1-x / 2 V(PO4) 3-x / 3 N x , wherein 0.001≤x≤0.05; M is Li and / or K, and N is selected from one or more of F, Cl, Br and I.
2. The positive electrode material according to claim 1, characterized in that In the molecular formula of the composite particles, 0.001≤x≤0.01; M is Li and / or K, and N is selected from one or more of F, Br and I.
3. The positive electrode material according to claim 2, characterized in that The molecular formula of the composite particles is Na4M 0.01 Mn 0.995 V(PO4) 2.997 N 0.01 , wherein M is Li and / or K, and N is selected from one or more of F, Br and I; Or, the molecular formula of the composite particles is Na4M 0.001 Mn 0.9995 V(PO4) 2.9997 N 0.001 , wherein M is Li and / or K, and N is F.
4. The positive electrode material according to claim 3, characterized in that The molecular formula of the composite particles is Na4K 0.01 Mn 0.995 V(PO4) 2.997 F 0.01 、Na4Li 0.01 Mn 0.995 V(PO4) 2.997 F 0.01 、Na4K 0.01 Mn 0.995 V(PO4) 2.997 Br 0.01 、Na4K 0.01 Mn 0.995 V(PO4) 2.997 I 0.01 、Na4K 0.001 Mn 0.9995 V(PO4) 2.9997 F 0.001 or Na4K 0.05 Mn 0.975 V(PO4) 2.983 F 0.05 .
5. A method for preparing a positive electrode material, characterized in that: The preparation method of the positive electrode material comprises: The sodium source, the doping element source, the manganese source, the vanadium source and the phosphorus source are prepared into a mixed slurry; The mixed slurry is dried and calcined in sequence to obtain the positive electrode material; Wherein, the positive electrode material comprises composite particles, and the molecular formula of the composite particles is Na4M x Mn 1-x / 2 V(PO4) 3-x / 3 N x , wherein 0.001≤x≤0.05; M is Li and / or K, and N is selected from one or more of F, Cl, Br and I.
6. The method for preparing the positive electrode material according to claim 5, characterized in that: The calcination comprises the following steps: The first stage of calcination, the temperature is 320℃~370℃, the holding time is 3h~5h; The second stage of calcination is at a temperature of 700°C to 750°C and the holding time is 7h to 9h.
7. The method for preparing the positive electrode material according to claim 6, characterized in that: The drying is spray drying, and the air inlet temperature of the spray drying is 200°C to 250°C, and the air outlet temperature is 100°C to 140°C.
8. The method for preparing the positive electrode material according to claim 7, characterized in that: The doping element source is selected from one or more of potassium fluoride, lithium fluoride, potassium bromide and potassium iodide; And / or, the sodium source is selected from one or more of sodium acetate, sodium carbonate, sodium hydroxide and sodium nitrate; and / or, the manganese source is selected from one or more of manganese acetate tetrahydrate, manganese nitrate, manganese phosphate and manganese oxalate; And / or, the vanadium source is selected from one or more of ammonium metavanadate, ammonium vanadate and ammonium sulfate; And / or, the phosphorus source is selected from one or more of diammonium phosphate, monoammonium phosphate, ammonium phosphate and phosphoric acid.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the positive electrode material according to any one of claims 1 to 4, or comprises the positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 5 to 8.
10. A sodium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Material with mixture of ions with sodium vanadium phosphate cathode material coated by carbon and preparing method thereof
CN106328911A
Preparation method and application of in-situ synergistic modified sodium manganese vanadium phosphate electrode material
CN119160867A
Positive electrode material, lithium ion secondary battery using the same, and method of manufacturing positive electrode material
JP2013077425A
Compositions and methods for manufacturing a cathode for a secondary battery
US20130078521A1
Cited By
Cathode material and preparation method therefor, cathode sheet and sodium-ion battery
US12738495B2